1990
DOI: 10.1007/bf00151707
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cardiovascular malformations in Finland

Abstract: The possible effects of genetic and environmental risk factors during pregnancy on the occurrence of cardiovascular malformations in the offspring was studied in 408 cases and 756 controls. The cases represented all registered cardiovascular malformations reported in Finland during 1982-1983. The controls were randomly selected from all babies born during the same period. Both the case and control mothers were interviewed by midwives approximately three months after delivery using a structured questionnaire. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 26 publications
5
46
1
3
Order By: Relevance
“…Our findings of associations between maternal chronic illnesses such as congenital heart disease and systemic connective tissue disorders and CHD were also in line with previous studies. 8,14,15,29,38 In addition, we observed that preexisting hypertension among mothers posed an elevated risk of certain subtypes of CHD. We also observed an association between maternal cigarette smoking and CHDs as in previous studies, 39,40 and the association was specific to particular subtypes of CHD.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our findings of associations between maternal chronic illnesses such as congenital heart disease and systemic connective tissue disorders and CHD were also in line with previous studies. 8,14,15,29,38 In addition, we observed that preexisting hypertension among mothers posed an elevated risk of certain subtypes of CHD. We also observed an association between maternal cigarette smoking and CHDs as in previous studies, 39,40 and the association was specific to particular subtypes of CHD.…”
Section: Discussionmentioning
confidence: 77%
“…An even smaller portion can be attributable to known environmental factors such as maternal rubella infection, although a few studies suggest that the fraction of cases attributable to identifiable factors may be as high as 30% for some types of heart defects. [12][13][14] Nevertheless, CHD prevention has been hampered by a limited understanding of modifiable risk factors.…”
mentioning
confidence: 99%
“…6 The National Public Health Institute in Helsinki retrospectively conducted a study in Finland of cases and controls born during 1982 to 1984. 7 In both of these casecontrol studies, information on potential exposures early in pregnancy was obtained by interview of the parents after the child was born. There were no available reliability or validation studies of the parental reports.…”
Section: Methodsmentioning
confidence: 99%
“…Reports of exposure to degreasing or other solvents have been associated with an increased risk of hypoplastic left heart syndrome, coarctation of the aorta, pulmonic stenosis, transposition of the great arteries with intact ventricular septum, tetralogy of Fallot, total anomalous pulmonary venous return, nonchromosomal atrioventricular septal defects, and Ebstein's anomaly. 6 Maternal reports of occupational exposure to organic solvents have been associated with an increased risk of VSDs 119,175 ; dyes, lacquers, and paints with conotruncal malformations 150 ; and mineral oil products with coarctation of the aorta. 176 Herbicides, Pesticides, and Rodenticides A study suggesting an association of maternal employment in the agricultural industry with an increased risk of conotruncal defects 36 suggested a possible association with chemicals used in agriculture.…”
Section: Organic Solventsmentioning
confidence: 99%
See 1 more Smart Citation